Pengaruh Substitusi Parsial Tepung Beras dengan Tepung Ubi Jalar Cilembu (Ipomea batatas (L). Lam Cv. Cilembu) terhadap Karakteristik Kue Apem Kukus - Suriani, Ni Putu; Kencana Putra, I Nengah; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p17, 2023)
Apem is a traditional Indonesian food known to the public as a snack made from rice flour. This study aimed to determine the effect of partial substitution of rice flour with cilembu sweet potato flour on the characteristics of apem cake and to know the best partial substitution to produce the best characteristics of apem cake. The design used in this study was a completely randomized design with a partial substitution treatment of rice flour and cilembu sweet potato flour which consists of 6 levels such as: 0%:100%, 10%:90%, 20%:80%, 30%:70%, 40%:60%, and 50%:50%. The treatment was repeated 3 times to obtain 18 units of the experiment. The data were analyzed by analyzed of variance and if the treatment affected on the variable significantly, then continued with the Duncan Multiple Range Test (DMRT). The result showed that partial substitution of rice flour with cilembu sweet potato flour had a significant effect on the content of moisture, ash, protein, fat, carbohydrate, crude fiber, swelling power, criteria hedonic of color, aroma, taste, and overall acceptance and criteria skor of color, aroma, texture and taste. The partial substitution of 50% produced apem cake with the best characteristics with moisture content 29.12%, ash content 0.51%, fat content 3.13%, protein content 2.85%, carbohydrate content 64.43%,  crude fiber content 6.29%, swelling power 55.30%, score of color yellow, strong cilembu sweet potato scented, soft texture, sweet taste and overall acceptance liked.